2022
DOI: 10.1021/acsami.1c18905
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Correlation between Electronic Properties and Sulfur Tolerance of Pt-Based Catalysts for Hydrogen Oxidation

Abstract: Renewable power-derived green hydrogen distributed via natural gas networks is considered one of the viable routes to drive the decarbonization of transportation and distributed power generation, while a trace amount of sulfur impurities is one of the key factors that affect the durability and life cycle expense of proton-exchange membrane fuel cells (PEMFCs) for end users. Herein, we explore the underlying effect of sulfur resistance for Ptbased hydrogen oxidation reaction (HOR) electrocatalysts devoted to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 61 publications
3
21
0
Order By: Relevance
“…A change in sulfur adsorption was reported for different alloys in literature; [26] for example, Lakhapatri and Abraham [26b] could show an increase of sulfur tolerance for a Ni‐based catalyst by Rh promotion. Furthermore, Ke et al [26a] . showed an improved sulfur tolerance of a PtCo bimetallic catalyst compared to a monometallic Pt catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…A change in sulfur adsorption was reported for different alloys in literature; [26] for example, Lakhapatri and Abraham [26b] could show an increase of sulfur tolerance for a Ni‐based catalyst by Rh promotion. Furthermore, Ke et al [26a] . showed an improved sulfur tolerance of a PtCo bimetallic catalyst compared to a monometallic Pt catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Both catalysts demonstrate a gradual decrease in ECSAs with the increase in testing time, but the degradation rate is much different (Figure a,b). Through fitting the curves of ECSA loss with time, the adsorption rate of S 2– on Pt sites was quantified according to our previous investigation results θ normalS = A ( 1 e k f s C S t ) where θ s presents the sulfur coverage on the Pt surface, C S is the concentration of S 2– , k fs is the adsorption rate constant, and t is time.…”
Section: Resultsmentioning
confidence: 99%
“…Although the adsorption energies of these sites adsorbed on or near Ru atoms are higher on the PtRu alloy surface compared with pure Pt, the lowered d-band center of Pt atoms induced by Ru leads to a weakened interaction between Pt and S and thus improves antipoisoning capability of PtRu/C. In our previous work, we explored the underlying effect of sulfur resistance for Pt-based HOR electrocatalysts and found that the sulfur tolerance of Pt-based catalysts is dependent on the electronic structure of Pt . Therefore, the PtRu alloy catalyst significantly reduces the absorbability on Pt active sites toward sulfur species through modification of the Pt electronic structure, making it a promising anode material for long-term application of PEMFCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuel cells, such as direct methanol fuel cells (DMFCs) and hydrogen oxygen fuel cells (HOFCs), are one of the most promising candidates to replace fossil fuels due to their nonpolluting and efficient energy conversion efficiency. The methanol oxidation reaction (MOR) and hydrogen oxidation reaction (HOR) belong to the anode reactions of DMFCs and HOFCs, respectively, and have been extensively studied. To date, Pt has been used as key materials for both MOR and HOR because of their superior activity compared to other metal materials. Thus, developing Pt-based electrocatalysts with high performance attracts extensive research and has great significance. …”
Section: Introductionmentioning
confidence: 99%